(Multi‐)Metallic Cluster Growth. Issue 34 (14th April 2018) - Weinert, Bastian; Mitzinger, Stefan; Dehnen, Stefanie
Abstract: This review article provides a survey of contemporary investigations on main group metal cluster formation, addressing homo‐ and heterometallic clusters (including small numbers of transition metal atoms), with or without an external ligand shell, thereby excluding clusters with non‐metal atoms as bridging ligands. Most of the studies reflected herein represent insights into the formation of intermediates from the starting material, or the final cluster formation from established intermediates. In rare cases, the entire process was suggested as a result of comprehensive, multi‐method elucidations. The article is to be understood as a state‐of‐the‐art report, as the subject matter is currently a rising field of research, which is still in its infancy, despite some early activities that date back to the 1980s. At the same time, the article intends to point toward both the importance and the feasibility of according studies, in order to encourage researchers to gain even more knowledge in this field. Only deep understanding of cluster formation will allow for design, and ultimately control, of their syntheses, with the long‐term goal of their optimization and purposeful application in catalysis or novel material synthesis. Abstract : Light into the black box : The formation of clusters that comprise exclusively (semi‐)metal atoms is still a mystery in most cases. As the elucidation of growth mechanisms is much more complicated than for organic molecules, entire formation cascades have usually not been explored. This review article provides a contemporary survey of the current knowledge in this field, addressing (multi‐)metallic clusters with or without protecting ligand shells.